Our women footballers storm into Cup decider - Xavier, Francis (New Sabah Times, 2016)
KOTA KINABALU: Sabah women advanced into the final of the 29th Tun Sharifah Rodziah Cup Football Tournament 2016 after trouncing hosts Kedah 5-0 at the Universiti Utara Malaysia (UUM) in Sintok yesterday;"